PENGARUH IKLAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK HALAL DENGAN ULASAN ONLINE KONSUMEN SEBAGAI VARIABEL MEDIASI - Ristina Tri Rahmawati (2021)
Indonesia is ranked second the largest halal cosmetic consumer country in the world with a total consumption of US$ 4 billion. In fact, Indonesia hasn't been first rank of the 10 indicator countries for halal pharmaceutical and cosmetic producers. Halal cosmetic manufacturers in Indonesia still ranked sixth, this condition is inversely to the total consumption of the Indonesian residential to halal cosmetics. This study aims to determine the effect of advertising and product quality on halal cosmetic purchasing decisions with online consumer reviews as a mediating variable. Research method is descriptive quantitative. Research test is the inner model, outer model, hypothesis testing and mediation testing with WarpPLS 7.0. Population is men and women who have bought and used halal cosmetics and domiciled in Jabodetabek. Samples are 210 people using purposive sampling. The results of a study found advertising, product quality, and online consumer review significant and positive on the purchasing decisions, and online consumer review was able to mediate advertising and product quality on purchasing decisions. The research is to increase Indonesian halal cosmetic manufacturers to become the world's main producer of halal cosmetics and innovate in the growth of halal cosmetics industry.